Uncertainty towards the disease of family caregivers of patients in palliative care : a scoping review (2020)
ABSTRACT: Objective: To know the development of the scientific evidence on the uncertainty towards the disease of family caregivers of patients in palliative care. Materials and methods: A descriptive scoping review. A search was conducted in the Embase, ScienceDirect, Medline, Academic Search Complete, Scopus databases, during the 2000-2019 period. The following MeSH terms were used: uncertainty, palliative care, end of life, nursing and caregiver. Fifty articles were selected after the criticism process. Results: Five thematic nuclei emerged: characterization of uncertainty in the caregiver, factors influencing uncertainty, resources to manage uncertainty, uncertainty assessment, and therapies and interventions to approach uncertainty. The higher scale of evidence is found in the characterization of uncertainty in the caregiver, and the voids direct the development of Nursing interventions on the uncertainty of the caregivers of individuals in palliative care. Conclusions: Although the factors influencing uncertainty towards the disease of the caregiver are widely explored, the evidence on the interventions that may help to reduce uncertainty towards the disease is still limited.